Association between physiological responses and heat shock protein 70 (HSP70) expressions in the vulnerable populations of Kuala Lumpur - Muhamad, Siti Nurfahirah; Lim, Fang Lee; Md Akim, Abdah; Karuppiah, Karmegam; Mohd Shabri, Nur Shabrina Azreen; How, Vivien (Taylor and Francis, 2024)
Continued heat exposure can cause physiological and cellular responses. This study investigated the association between physiological responses and heat shock protein 70 (HSP70) expressions in Kuala Lumpur's urban vulnerable population. We conducted a cross-sectional study involving 54 participants from four areas classified as experiencing moderate to strong heat stress. Physiological measurements included core body temperature, heart rate, and diastolic and systolic blood pressure. RT-qPCR and ELISA were also performed on blood samples to assess HSP70 gene and protein expressions. Despite indoor heat stress, participants maintained normal physiological parameters while there were significant indications of HSP70 expression at both the gene and protein levels. However, our study found no significant correlation (p > 0.05) between physiological responses and HSP70 expressions. This study shows no interaction between physiological responses and HSP70 expressions in the study population, revealing the complex mechanisms of indoor heat stress in vulnerable individuals.